LA REPÚBLICA INDEPENDENTE, EL PODER CONSTITUYENTE Y EL HÉROE DE LA EMANCIPACIÓN. - Vermeren, Patrice (Revista de Filosofía (00348236), 2011)
Who is a hero of emancipation? Rousseau contrasted the ancient hero, a triumphant worrier who defeats the enemies of his country, with the true hero, the one who is able to surrender his singularity in order better to promote the collective agency of a sovereign people. The French revolution, according to Miguel Abensour, redefines political heroism as the ability to initiate something in the unpredictability of the result, establishing therefore a new society in which the figures of the hero and the legislator coincide, broaching an enigmatic relationship between bondage and freedom, and establishing an order that supersedes the divisions generated by unjust desires. But if "the hero is the true subject of modernity" (Walter Benjamin quoting Baudelaire) is not the possibility of heroism in a prosaic modern post-revolutionary society the key issue of the nineteenth century? What to think of a heroic figure like Simon Bolivar, - the usurper of the title Libertador (Benjamin Constant)? The Napoleon of the retreats (Karl Marx)? The accoucheur of the emancipation, (Pierre Leroux and Jean Reynaud's New Encyclopedia)? The emancipating luminary of the American people fallen in bondage (Juan Montalvo)?